Cross-national aspects of cyberbullying victimization among 14-17-year-old adolescents across seven European countries - Athanasiou, K.; Melegkovits, E.; Andrie, E.K.; Magoulas, C.; Tzavara, C.K.; Richardson, C.; Greydanus, D.; Tsolia, M.; Tsitsika, A.K. (2018)
Background: The increasing use of the Internet and social network sites (SNS) has created a new domain of socio-emotional development for adolescents. The aim of this cross-sectional study was to explore cybervictimization across seven European countries, in relation to socio-demographic, Internet use and psychosocial variables. Methods: A cross-sectional school-based study was conducted in the participating countries: Germany, Greece, Iceland the Netherlands, Poland, Romania and Spain. Anonymous self-completed questionnaires included sociodemographic data, internet usage characteristics, school achievement, parental control, the Internet Addiction Test and Achenbach's Youth Self-Report. Results: The highest rate of cyber victimization was found in Romania (37.3%) and the lowest in Spain (13.3%). Multiple logistic regression analyses gave differing results between countries. In Romania, Poland and Germany cyberbullying victimization was associated with SNS use, whereas Internet use was associated with increased odds of cybervictimization only in Romania. Cybervictimization was associated with greater internalizing behavior problems in all countries analysed, and with externalizing problems in all except Romania. Conclusions: Cyberbullying victimization is an on-going problem, which is subject to country-specific socio-demographic factors and diverse patterns of current Internet use and its development. Preventive measures should emphasize the integration of Internet communication technology education in educational contexts, and focus on the consistent association between cybervictimization and internalizing and externalizing difficulties. © 2018 The Author(s).